The Effect of Taxes on the Pricing of Defaultable Debt - LIM, Kian Guan (Institutional Knowledge at Singapore Management University, 2003)
Empirical studies have documented the dependence of corporate credit spreads on default risk, equity premiums, and taxes. However, taxes have previously not been incorporated into reduced-form credit risk models. Therefore, we first extend the existing literature by considering a default intensity that depends on taxes as well as the default-free short rate and a market index. Consequently, we establish a theoretical basis to explain previous empirical findings regarding the significant impact of taxation on defaultable bond prices. Unlike previous models, tax implications for defaultable debt cannot be constructed from a sum of tax effects on zero coupon bonds. Our empirical tests then illustrate the importance of taxation. In particular, the impact of taxation increases as a function of the debt's maturity and coupon rate.